ANALISIS PREFERENSI MASYARAKAT TERHADAP RESTORAN CEPAT SAJI DI KOTA BOGOR - Sri Hartini; Lesti Hartati (Universitas Pakuan, 2017)
ABSTRACTThe objectives of this research are: (1) to identify the most important environmental factors that led to a variety of consumer preferences for fast food restaurants in Bogor; (2) to measure the relative performance of consumer satisfaction attribute in fast food restaurant industry in Bogor by using approach of importance performance analysis; and (3) to identify the pattern of competition among fast food restaurants in Bogor City with the use of SPSS scoring method. Data analysis method used is Fischbein analysis consist of quantitative analysis and qualitative analysis. The results showed that: 1) hygiene factors should be put forward because the concept of fast food restaurants attract more consumers from middle to upper economic level, and of course it is critical to give an assessment of the condition or circumstances in all aspects of the service from fast food restaurants; 2) the level of service provided to the consumer most attributes are in the low priority position matrix with the percentage of 53%, the attribute on the matrix to maintain the achievement is in the second with the percentage of 33%, followed by the main priority attribute is only 9% and the last attribute on the matrix excessive with percentage of 5%. This means there are still many attributes that do not have significant effectiveness to the services provided by each attribute; 3) can be determined the average total scoring of KFC restaurant (20.56, 14%), McD restaurant (18.29, 12%), Pizza Hut restaurant (16.67, 11%), Trio restaurant (15.98,11%), restaurant of Simpang Raya (15.96,11%), Burger Kings restaurant(15.87,10%, Rumah Anai restaurant, (15.18; 10%), and Dominos restaurant (14.83,10%).Keywords: Community Preference, Fast Food Restaurant, and Bogor City